Delineating the technosphere: definition, categorization, and characteristics - E. D. Galbraith; E. D. Galbraith; E. D. Galbraith; A. A. Faisal; T. Matitia; W. Fajzel; I. Hatton; H. Haberl; F. Krausmann; D. Wiedenhofer (Earth System Dynamics, 2025)
The global assemblage of human-created buildings, infrastructure, machinery, and other artifacts has been called the “technosphere”, and it plays a major role in the present-day dynamics of the Earth system. The technosphere enables the rapid extraction of natural resources and the combustion of fossil fuels, impacting biodiversity and causing climate change while generating copious amounts of waste materials. At the same time, the technosphere supports humans in many ways, including the provision of food, shelter, transportation, and long-distance communication, and it is the main component of material wealth. Despite its importance, Earth system science has been slow to explicitly incorporate the technosphere as an integrated part of its conceptual and quantitative frameworks. Here we propose a refined definition of the technosphere, intended to assist in developing functional integration with other Earth system spheres as well as social sciences. We also suggest a categorization system for the things that make up the technosphere based on how their end uses support human motivations. Given the formal definition and resolved categorization, we delineate basic attributes of the technosphere, including its mass distribution among categories and across the Earth surface, and discuss its first-order temporal dynamics. In particular, of the 1-trillion-tonne technosphere mass, we estimate that roughly one-half is buildings and one-third transportation infrastructure, both of which we map globally at 1° resolution. Movable entities, mostly composed of vehicles, vessels, and machinery, account for less than 2 % of the total technosphere mass yet are comparable to the biomass of all animals on Earth. We show that reconstructions of the technosphere since 1900 are consistent with an autocatalytic process, resulting in exponential growth with a long-run increase of > 3 % yr−1, equivalent to a 20-year doubling time. Building a stronger quantitative understanding of the technosphere can help to better integrate it within Earth system science while bridging natural and social sciences to support physically plausible pathways towards sustainability and human wellbeing.